Metode Penenganan Dan Penyelesaian Kekerasan Terhadap Perempuan Dalam Rumah Tangga Di Yogyakarta - Zulkipli Lessy; Linah Khairiyah Pary (State Institute of Islamic Studies (IAIN) Salatiga, 2012)
The study examines the following concerns: what the various types of family barrasment? What are obstacles encontered by kantor peberdayaan perempuan (KPP) Daerah Istimewa Yogyakarta (DIY) in dealing with violence against women; how does the KPP counter these obstacles? Using the naturalistic-qualitative approach, data was gathered via interviewing, observation, and documentation. Findings show that barrasment of women can be physical, economic or sexual. A holistic treatment was initiated by means of medical, sosial, psycho- logical, marriage and legal counseling. Obstacles encountered by the counselors in dealing with victims were both internal and external